Adjudicating over anarchy : judicial remedies, compliance, and enforcement in international law / Geraldo Vidigal, University of Amsterdam. - Vidigal, Geraldo (Cambridge studies in international and comparative law ;, 2026)
Geraldo Vidigal thoroughly examines the judicial powers of international courts and tribunals and how these powers are used in practice. Without access to state-backed enforcement measures, international adjudicators must rely on their authority to influence real-world outcomes. The book reviews, and offers a comprehensive theory for, the various social mechanisms that explain why and how international judicial pronouncements affect the behaviour of states, influencing the views of individuals within states as well as changing states' mutual expectations of cooperative and sanction-worthy behaviour. The book considers how judicial remedies can induce compliance by targeting specific areas of disagreement, interpreting obligations, declaring violations, and establishing how wrongdoer states must offset unlawful injury. An often untapped type of remedy relies on the ability of courts to determine permissible responses to breach: what measures other actors may take to respond to violations, compelling wrongdoers to comply with their obligations and provide redress for injury.